“La suspensión condicional del proceso como medida alternativa a la pena, incidencia de la inobservancia de los principios constitucionales por parte de los administradores de justicia”. - Labanda Escobar, Santiago Eduardo (2023)
In the present investigation, the Constitutional Principles have been identified, same that must be observed by the Justice Administrators at the moment to make decisions on the applicability of alternative methods to deprivation of Freedom, thus, Article 630 of the Comprehensive Organic Criminal Code establishes the parameters that judges must apply to the person in conflict with the law to that this can be benefited from the conditional suspension of the sentence. But in certain cases these principles, as well as the rules established in Art. 630 of the Comprehensive Organic Criminal Code, have been disregarded by the Administrators of Justice, the same ones that have denied this benefit of the conditional suspension of the penalty based on what is established in the first numeral of Art. 630 of the COIP, since, the custodial sentence "provided for the conduct" does not exceed than five years, that is, if a person who was sentenced as an accomplice to a crime of theft that is typified in Art.